Carry Trade and Credit Crunch in the Spanish Economy - Alonso, Fernando; Blázquez, Pablo (Papeles de Europa, 2014)
This paper presents some factors which contribute and originate the current credit restrictions to companies and consumption during the crisis phase that have affected the Spanish economy is now experiencing. It analyzes key questions that lead to the current situation as policies applied by Central Banks before and during the crisis period, sectorial distribution of the credit, and performance of credit in commercial banks in their risk and liquidity policies. The quantitative data shows a clear link between two phenomena detected and integrated in the Spanish Financial System: the “carry trade” or the use of credit by the European Central Bank to buy great amounts of Public Debt caused the “credit crunch” with levels much lower than those existing in the other countries of OECD originated in base to the commercial banks behavior in their transmission role of the monetary policy.